Predictors of Participation in the U.S. Department of Agriculture Summer Meal Programs: An Examination of Outreach Strategies and Meal Distribution Methods During COVID-19 - Brooke L. Bennett, PhD; Juliana F.W. Cohen, ScD; Tatiana Andreyeva, PhD; Julia Esposito, BA; Kara Burkholder, MPH; Sandra M. Chafouleas, PhD; Marlene B. Schwartz, PhD (Elsevier, 2023)
Introduction: Significantly fewer children participate in the U.S. Department of Agriculture-sponsored summer meal programs than in the federal school meal programs during the academic year. During the summer of 2021, several pandemic-related waivers supported more flexible operations for summer meal programs, such as allowing grab-and-go meals and the distribution of meals for multiple days at once. This study assessed how summer meal site characteristics and geographically targeted outreach methods were associated with summer meals served in 2021 in Connecticut. Methods: Weekly meal count data were requested from all sponsors of the Summer Food Service Program and the National School Lunch Program Seamless Summer Option. Data were received from 78 sponsors with 763 sites. Geographically targeted outreach (e.g., billboards, bus ads, and flyers) was tracked by location each week. Mixed methods ANOVA was used to examine the predictive value of outreach efforts, program characteristics, and meal distribution methods on meals served each week. The program characteristics examined included the hours open per week, the number of weeks serving meals, the maximum number of meals distributed at one time, and the number of open and closed sites in a school district. Results: Between June 21 and August 20, 2021, a total of 1,188,669 breakfasts and 1,389,347 lunches were served. Sites that were open more hours per week (mean=7.60 hours per week; range=0.17-35) and gave multiple meals to parents at each visit (mean=4.68 meals; range=1-15) reported greater rates of meal distribution. The outreach efforts assessed were not significantly associated with changes in meal distribution at nearby sites. Conclusions: The U.S. Department of Agriculture's waivers in response to COVID-19 permitted extended operating hours and multiple-meal distribution. These operational flexibilities should be considered for permanent regulation changes owing to their positive association with summer meal participation.